Sociodemographic and clinical profile of patients submitted to cardiac surgery (Research, Society and Development, 2022)
Cardiovascular diseases (CVD) constitute the main cause of death in Brazil. The knowledge of the main types of heart attacks, as well as the possible treatments of these pathologies, is necessary. The work is justified by the importance of the theme and the lack of publications of this specific subject in view of its magnitude. The objective was to know the sociodemographic and clinical profile of patients who need to undergo some type of cardiac surgery. This is a literature review of the integrative type, carried out in April and May of 2019, with a systematic search in Latin American and Caribbean Literature in Health Sciences, Medical Literature Analisys and Retrieval System Online and Base of Nursing Data. Twelve articles were included, which answered the research question and met the inclusion criteria. He performed the data content analysis, which made it possible to divide the findings into categories. Despite the insipid literature in the last five years, it is observed that the most frequently performed surgery is myocardial revascularization, sociodemographically, a significant majority of the patients are men, sexagenarians, married and with elementary school, clinically have a family history and associated comorbidities.